Wear mapping mechanism mapping for diesel-diluted biolubricant / Mohamad Firdaus Saharudin - Mohamad Firdaus , Saharudin (2022)
As a result of concerns about fossil fuel depletion and climate change, tough legislation requiring automobiles to utilize renewable fuels, mainly bioethanol, have been enacted. In fact, the friction caused by the piston ring and the cylinder wall, which is the biggest source of friction in an engine, is caused by a lot of fuel getting into the lubricant from unburned fuel, which has a lot of heat of vaporization to make it easier for fuel to get into the crankcase. Recently, bio-based lubricant has been mixed with gasoline at ever higher concentrations, and the amount of fuel that builds up in the crankcase is significant. It is important to investigate the tribology of wear mechanism mapping for diesel-diluted bio-lubricant. This research shows how biolubricant and special machines can be used to investigate how things wear. Many goals were met in this study, which looked at how fuel dilution in bio-lubricant affected performance, physicochemical and oil ageing, as well as how it affected the lubricant itself. The fourball tester tribotester machine can be used to look at friction and wear in bio-lubricant oils. Because of its excellent lubricity and resistance to oxidation, the trimethylolpropane trioleate (TMPTO) ester was chosen as the bio-based base stock in this study. The esterification of oleic acid with TMP alcohol yielded TMPTO. From this study, the last goal is to make a wear map of the steel ball. The fourball tester method was used in the research, which is a standard way to figure out how lubricant diesel fuel is used. For each fuel sample, microscopic views of the test ball wear scars, as well as the areas that have been considered when measuring the diameters of the scars, were shown. When make a wear map, compare two samples that are in different conditions, like temperature and rotation speed. This wear map is the main goal of this project.